SISTEM PEMBELIAN KREDIT UNTUK FOOD AND BEVERAGE PADA BEST WESTERN PLUS KEMAYORAN HOTEL - Anisa Wulandira; A Sudrajat (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
A system is a collection or set of elements, components or variables that are organized, interact with each other, are interdependent and integrated. Meanwhile, credit purchases are purchases made by companies by gradually repaying the payment fee. Food and Beverage or commonly abbreviated as F&B is a department in hospitality that focuses on food and beverage services to achieve customer satisfaction. Of course, the materials used in the F&B department must be provided by the purchasing department. This study aims to fulfill a final assignment in a diploma three accounting study program, in addition to knowing the credit purchasing system for food and beverage that exists at the Best Western Plus Kemayoran hotel. By using the observation method, documentation method, and literature study in conducting this research. It can be concluded from the results of this study, that purchase requests for food and beverage are made by the kitchen department, and the purchasing department will make purchases on credit in order to reduce hotel expenses. Due to requests that are almost every day.